POLITICAL AND MEDIA INTERACTION IN IRAQ AND THE ELEMENT OF CONTINUITY IN IRAQI MEDIA POLICIES - Oudah, Yaareb Qahtan (Journal of Social Science, 2026)
Objective: This test lights up the intersection of media and politics in the Iraqi context and introduces adaptive continuity theory to explain why the field was )notified by enabling media reform, which has been fundamentally transformed. A longitudinal study of four Iraqi governments (2014-2023) systematically analyzes media coverage, examining how well sitting leaders meet objections from various sectors. The study also includes field research data and media discourse analysis to understand the influence of political control on the media system, as well as the relationship between party-state control and media message production. Method: The study reveals that media reforms did not change the MMC institutional corrections over a long period. Instead, they highlighted how these institutions produce media actors and entrench past propaganda relations. Additionally, media outlets are under greater political pressure, and party-state relationships continue to dominate media content, especially in mainstream media. Result: Social media, although breaking the former monopoly on information, has been manipulated by those forces that originally maintained that monopoly. The study presents a paradox of social media: it has democratized information but also enabled those in power to control and limit the dissemination of information. Novelty: The analysis concludes that the media's credibility crisis, fueled by fake news and government censorship, prevents it from fulfilling its oversight function. The study proposes that further reform, without radical change to protect media institutions from partisan control, will remain ineffective.